TRANSFORMATIONAL LEADERSHIP, EMPLOYMENT COMPETENCY AND CAREER LEVELS AS PREDICTORS OF JOB SATISFACTION AND EMPLOYEE PERFORMANCE: An Empirical Study - Khamaidi Khamaidi; I Dewa Ketut Raka Ardiana; M.Sihab Ridwan (STIE Mahardhika, 2022)
The aim of this study is to explore the transformational relationship of leadership, job competence, and career path to job satisfaction and employee performance, and explore the relationship of job satisfaction in employee performance. The method used in this study is quantitative by focusing on hypothesis testing. While the sample used is as many as 91 employees with saturated sampling techniques. The next analysis model used is Partial Least Square (PLS). The findings of this study reveal that transformational leadership, work competence, and career levels are proven to have a positive and significant influence on job satisfaction and employee performance. Likewise, the relationship of job satisfaction to employee performance is positive and significant. In addition, the implications of this research have been discussed in this study.